A multicenter randomized controlled trial of endovascular therapy following imaging evaluation for ischemic stroke (DEFUSE 3). Issue 8 (October 2017) - Albers, Gregory W; Lansberg, Maarten G; Kemp, Stephanie; Tsai, Jenny P; Lavori, Phil; Christensen, Soren; Mlynash, Michael; Kim, Sun; Hamilton, Scott; Yeatts, Sharon D; Palesch, Yuko; Bammer, Roland; et al.
Rationale: Early reperfusion in patients experiencing acute ischemic stroke is effective in patients with large vessel occlusion. No randomized data are available regarding the safety and efficacy of endovascular therapy beyond 6 h from symptom onset. Aim: The aim of the study is to demonstrate that, among patients with large vessel anterior circulation occlusion who have a favorable imaging profile on computed tomography perfusion or magnetic resonance imaging, endovascular therapy with a Food and Drug Administration 510 K-cleared mechanical thrombectomy device reduces the degree of disability three months post stroke. Design: The study is a prospective, randomized, multicenter, phase III, adaptive, blinded endpoint, controlled trial. A maximum of 476 patients will be randomized and treated between 6 and 16 h of symptom onset. Procedures: Patients undergo imaging with computed tomography perfusion or magnetic resonance diffusion/perfusion, and automated software (RAPID) determines if the Target Mismatch Profile is present. Patients who meet both clinical and imaging selection criteria are randomized 1:1 to endovascular therapy plus medical management or medical management alone. The individual endovascular therapist chooses the specific device (or devices) employed. Study outcomes: The primary endpoint is the distribution of scores on the modified Rankin Scale at day 90. The secondary endpoint is the proportion of patients with modified Rankin Scale 0–2 at day 90 (indicating functional independence). Analysis: Statistical analysis for the primary endpoint will be conducted using a normal approximation of the Wilcoxon–Mann–Whitney test (the generalized likelihood ratio test).